Deconstructing Traumatic Mission Experiences: Identifying Critical Incidents and Their Relevance for the Mental and Physical Health Among Emergency Medical Service Personnel - Behnke, Alexander; Rojas, Roberto; Karrasch, Sarah; Hitzler, Melissa; Kolassa, Iris-Tatjana (Frontiers in Psychology, 2019)
Emergency medical service (EMS) personnel frequently encounter emotionally stressful or even traumatic incidents in their line of duty. In this study, a checklist of emotionally stressful events for the German EMS was introduced. A mixed-method approach was used to identify mission events that were critical for the development of mental and physical stress symptoms. Data were collected in a cross-sectional sample of 102 EMS employees. A quantitative content analysis of the participants’ worst experiences on duty indicated, traumatic missions to be a concatenation of two to five emotionally stressful events. Rescue missions were experienced as traumatic if (i) EMS personnel became victims of attacks or threats; (ii) certain circumstances caused them to give up their professional detachment from patients; (iii) EMS personnel perceived the overall mission as exceptionally tragic. In subsequent correlation analyses, the corresponding checklist items showed consistent positive associations with the posttraumatic, depressive and physical stress symptoms among the study cohort. Within the exploratory regressions, the sum score of critical on-duty exposures contributed incrementally to the prediction of mental and physical stress symptoms when nonwork-related trauma exposure and perceived social support were also considered. Findings point towards the importance of considering the cumulative burden of critical incidents for the long-term health of EMS personnel. Future research is needed to investigate, how on-duty trauma affects the social support EMS personnel received from their work and personal relationships.